If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 1.2r + 2(3.4r + -1) = 1.4r + 6 Reorder the terms: 1.2r + 2(-1 + 3.4r) = 1.4r + 6 1.2r + (-1 * 2 + 3.4r * 2) = 1.4r + 6 1.2r + (-2 + 6.8r) = 1.4r + 6 Reorder the terms: -2 + 1.2r + 6.8r = 1.4r + 6 Combine like terms: 1.2r + 6.8r = 8r -2 + 8r = 1.4r + 6 Reorder the terms: -2 + 8r = 6 + 1.4r Solving -2 + 8r = 6 + 1.4r Solving for variable 'r'. Move all terms containing r to the left, all other terms to the right. Add '-1.4r' to each side of the equation. -2 + 8r + -1.4r = 6 + 1.4r + -1.4r Combine like terms: 8r + -1.4r = 6.6r -2 + 6.6r = 6 + 1.4r + -1.4r Combine like terms: 1.4r + -1.4r = 0.0 -2 + 6.6r = 6 + 0.0 -2 + 6.6r = 6 Add '2' to each side of the equation. -2 + 2 + 6.6r = 6 + 2 Combine like terms: -2 + 2 = 0 0 + 6.6r = 6 + 2 6.6r = 6 + 2 Combine like terms: 6 + 2 = 8 6.6r = 8 Divide each side by '6.6'. r = 1.212121212 Simplifying r = 1.212121212
| 16-45=4(x-2)-9 | | b=c+24 | | -8y+3y-(10)+2y=11 | | 5+(n+9)=-3 | | 15=2t+.806t | | 25+50h=8 | | 3y^2+27y+60=0 | | 3(x+2)-10(x+10)=-7-8 | | 4t=2(7x+15) | | 6(3x+7)=3x+2-5x | | 3+5h=5 | | 10(x-2)=2(x+9) | | 34-0.5d=26 | | 2.1(a+2)=2.1a+4.2 | | 4-4(x-2)=-1+3(x-5+2) | | 3n-6-6+2n=4n-12 | | 0=-4x+21-x^2 | | 2x(5.83)=x(5.83) | | 5x=8(6x-1)-35 | | 4x^3+12x^2+2=0 | | 11-(-10)-5/6= | | 4[2-3(2x+4)]=5x | | (y-6)-(5y-7)= | | log(x)=1.9 | | y=9x^2-36 | | -40=6x+8 | | 5(1x+7)=20 | | (y-5)-(5y-7)= | | 3x+10=15x-8 | | 5(-2x+8)=-50 | | 4(2+2)= | | 2x+3-5x+7=1 |